Effectiveness of Immersive Technology in Enhancing Students' Learning Experiences in Public Secondary Schools - Samuel Muhammed Enefu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
The study investigated the effectiveness of immersive technology in enhancing students' learning experiences in public secondary schools in Kogi East.This study adopted a descriptive survey design, the population of the study comprise of all the senior secondary school students and teachers from secondary schools in the Kogi East Senatorial District, which comprises nine local government areas (LGAs): Ankpa, Bassa, Dekina, Ibaji, Idah, Igalamela-Odolu, Ofu, Olamaboro, and Omala. The sample is three hundred and eighty-five, (385), to arrive at this, purposive sampling technique was used to select (30) secondary students each from the secondary schools, bringing the number to 330 and five teaching staff each bringing the number of teachings to 55. Data were collected using a 12-items structured questionnaire titled Effectiveness of Immersive Technology in Enhancing Students Learning Experience Questionnaire (EITESLEQ). The instrument for data collection was validated by three experts two from Measurement and Evaluation and one in the Department of Educational Foundations in University of Nigeria, Nsukka and Cronbach Alpha was used to determine the reliability index of 0.78. The two research questions were answered using mean scores while the two hypotheses were tested using t-test analysis at .05 Alpha levels. The findings reveal that, immersive technology experience enhances student's learning experience in secondary schools and that there are challenges limiting teachers’ use of immersive technology experience in enhancing students' learning experience in secondary schools. Finally, based on the findings, the following recommendations were made; the improvement of teachers' ICT abilities through training, need for continued professional development in information and communication technology and school management teams in the township and rural secondary schools will have to stay ahead of the unfolding situation by devising strategies and organizing means to mitigate the effects of the unknown world being anticipated, going forward.